1983
DOI: 10.1002/art.1780260503
|View full text |Cite
|
Sign up to set email alerts
|

IgG and IgM Rheumatoid Factors in Rheumatoid Arthritis

Abstract: Penicillamine treatment of patients with rheumatoid arthritis (RA) leads to falling titers of agglutinating IgM rheumatoid factor (RF), but its effect on IgG RF has not been described. Using specific solid phase radioimmunoassays, we have determined serial levels of IgM RF and IgG RF in 18 patients receiving penicillamine for 1 year, and correlated the results with the change in RA activity. Mean IgM RF levels fell to 76 f 10% (mean & SEM) after 3 months, and 30 k 5% of the pretreatment value after 1 year of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

1984
1984
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(5 citation statements)
references
References 22 publications
0
3
0
2
Order By: Relevance
“…A reduction of IgM RF, IgG RF, and IgA RF levels after 1 year of methotrexate treatment was also reported by Spadaro and co‐workers 22 . Other studies have evaluated the effect of penicillamine, gold salts, minocycline, and sulphasalazine on RF levels showing that treatment can decrease the production of IgM RF and, to a lesser extent, of IgA RF and IgG RF 7,21–24 . Recently, Mikuls et al showed a good correlation between clinical response and a drop in IgM RF levels in 64 patients treated with different DMARDs for about 1 year 23 …”
Section: Changes In Radiofrequency During Anti‐tnf‐α Therapymentioning
confidence: 57%
“…A reduction of IgM RF, IgG RF, and IgA RF levels after 1 year of methotrexate treatment was also reported by Spadaro and co‐workers 22 . Other studies have evaluated the effect of penicillamine, gold salts, minocycline, and sulphasalazine on RF levels showing that treatment can decrease the production of IgM RF and, to a lesser extent, of IgA RF and IgG RF 7,21–24 . Recently, Mikuls et al showed a good correlation between clinical response and a drop in IgM RF levels in 64 patients treated with different DMARDs for about 1 year 23 …”
Section: Changes In Radiofrequency During Anti‐tnf‐α Therapymentioning
confidence: 57%
“…However, more recent studies have shown that this RF isotype is also present and may be produced in nonmucosal compartments.25 70 71 Furthermore, evidence for local production of both IgAl RF and IgA2 RF subclasses in mucosal (saliva) and in non-mucosal (synovial fluid) compartments has been put forward, and a predominance of IgA2 RF production in salivary glands compared with synovial fluid was observed. 25 Reduction of RF has been demonstrated after treatment with SASP and other antirheumatic agents, for example D-penicillamine, gold, and methotrexate.3 53 55 [72][73][74][75][76] Because the changes in IgA RF and IgM RF did not correlate with the respective changes in serum immunoglobulin concentrations in the SASP treated patients (data not shown), the reductions in RF are not considered to be related to the changes in the overall production of immunoglobulins. Rather, it seems plausible that SASP directly inhibits RF production, an influence that is selective for IgA RF and IgM RF-committed B cells, as synthesis of IgG RF was not affected.…”
Section: Determination Of Immunoglobulins In Saliva and Jejunal Aspiratementioning
confidence: 99%
“…Complement-derived activation fragments, particularly C5a (Wedmore & Williams, 1981), are likely to be important inflammatory mediators in rheumatoid arthritis (Moxley & Ruddy, 1987). D(-)-Penicillamine [D(-)-/fl,-dimethylcysteine] has been used as an anti-rheumatic agent, but its mechanism of action is not clearly established, although reduction of disulphide bridges in Rheumatoid Factor (Wernick et al, 1983) and inhibition of collagen cross-linking (Nimni et al, 1972) have been suggested. One major problem with penicillamine as an anti-rheumatic drug is that there is a high incidence of patients suffering adverse side effects, which include problems in clearance of immune complexes with resulting proteinuria and glomerulonephritis (Andrews et al, 1973;Davison et al, 1977;Kean et al, 1980).…”
Section: Introductionmentioning
confidence: 98%